Role of epigenetic alterations in the pathogenesis of Barrett’s esophagus and esophageal adenocarcinoma - Agarwal, Archana (e-Century Publishing Corporation, 2012)
Barrett’s esophagus, a pre-malignant condition that can lead to esophageal adenocarcinoma, is characterized by histological changes in the normal squamous epithelium of the esophagus. Numerous molecular changes occur during the multistage conversion of Barrett’s metaplasia to dysplasia and frank adenocarcinoma. Epigenetic changes, especially changes in DNA methylation are widespread during this process. Aberrant DNA methylation has been shown to occur at promoters of tumor suppressor genes, adhesion molecules and DNA repair genes during Barrett’s esophagus. These epigenetic alterations can be used as molecular biomarkers for risk stratification and early detection of esophageal adenocarcinoma. We also show that genome wide analysis of methylation surprisingly reveals that global hypomethylation and not hypermethylation is the dominant change during Barrett’s metaplasia. The transformation of Barrett’s esophagus to frank adenocarcinoma is in turn characterized by much smaller wave of selective promoter hypermethylation. These studies reveal many novel, potential targets for new therapies and illustrate the utility of incorporating these epigenetic changes as biomarkers during endoscopic surveillance interval for patients with Barrett’s esophagus.